FAKTOR PENYEBAB PERMUKIMAN KUMUH DI KELURAHAN BAGAN DELI BELAWAN KOTA MEDAN - Putra, Kaspan Eka; Andriana, Melly (Talenta Publisher, 2017)
Settlement Region and Urban slum is a big problem that must be solved in the Development Process. In Medan, there are some urban slums, one of these slum areas is in Bagan Deli, Lingkungan Lorong Mesjid Village, Medan Belawan. This study aims to determine the factors that caused untidiness in this slum area. Methods of the study was conducted with direct observation on the region. The data that already obtained are used as basis of analysis for answering the problems of the study, namely to know the factors that caused untidiness in this slum area. From the results of research findings that there are 5 factors that cause untidiness, that are population density factor, income factor, land ownership factor, occupant behavior factor, and care services factors include the availability of facilities and infrastructure. After knowing the factors of untidiness in slum area, then will make the best solutions, that is revitalization (rebuilding) operating physical and socio-economic.